[Photograph and letter, sent from Hearst to Morgan] - William Randolph Hearst::::::author::: (1936)
Caption written by Hearst under photograph reads: 'The big plane we traveled in for seven and one half hours -- over Spain over France over the Channel at Havre and in the fog in England.'